User-centered gamification: how to design, develop and evaluate it - Carolina Tome´ Klock, Ana; Gasparini, Isabela; Soares Pimenta, Marcelo (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2018: Anais Estendidos do XVII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2018)
Gamification is the use of game elements in contexts which the main purpose is not playful and it has been widely applied in order to motivate and engage users [5][11]. However, since each user has different characteristics, the user experience during the interaction with these game elements becomes singular and it does not always have the expected outcome. Many studies point out the influence of users profile on the effectiveness of gamification in relation to the purpose of its application [1][2][4][3][6][7][9], but surprisingly little has been explored about the processes of design, development and evaluation of the user-centered gamification to promote a better user experience and, consequently, a greater motivation and engagement [8]. Thus, this course aims to cover personal, functional, psychological, temporal, playful, implementable and evaluative properties of gamification in order to enable the participants to design, develop and evaluate a user-centered gamification, while allowing the improvement of the gamification results. For this, the methodology to be employed by this course involves two parts: theoretical and practical. In the theoretical part, the exposition of concepts related to gamification will be carried out, followed by examples, in an interactive way with the participants. In the second part, participants will be invited to bring examples of scenarios that they would like to work on and the concepts presented will be put into practice so that the public can participate and share their experiences while designing the usercentered gamification.